Question
upstudy study bank question image url

\( \left.\begin{array}{l}\text { DADAS LAS SIGUIENTES MATRICES DE } 1 \times 1 \text { REALIZA LAS SIGUIENTES OPERACIONES: } \\ \mathrm{A}=\left[\begin{array}{cc}11 & -9 \\ 7 & -10\end{array}\right] \\ \mathrm{A}+\mathrm{B} \\ \mathrm{B}+\mathrm{C} \\ \mathrm{A}-\mathrm{B}\end{array} \begin{array}{ll}-4 & -10 \\ -3 & -10\end{array}\right] \quad \mathrm{C}=\left[\begin{array}{cc}-1 & -3 \\ 1 & 3\end{array}\right] \)

Ask by Herrera Warren. in Mexico
Feb 26,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

A + B = [7 –19]     [4 –20] B + C = [–5 –13]     [–2 –7] A – B = [15 1]     [10 0]

Solution

Dadas las matrices   A = [ 11   –9 ]     [  7  –10 ]   B = [ –4  –10 ]     [ –3  –10 ]   C = [ –1   –3 ]     [  1    3 ] realizaremos las siguientes operaciones: 1) A + B   Se suman elemento a elemento:   • Primera fila, primera columna: 11 + (–4) = 7   • Primera fila, segunda columna: –9 + (–10) = –19   • Segunda fila, primera columna: 7 + (–3) = 4   • Segunda fila, segunda columna: –10 + (–10) = –20   Por lo tanto,   A + B = [ 7   –19 ]        [ 4   –20 ] 2) B + C   Sumamos elemento a elemento:   • Primera fila, primera columna: –4 + (–1) = –5   • Primera fila, segunda columna: –10 + (–3) = –13   • Segunda fila, primera columna: –3 + 1 = –2   • Segunda fila, segunda columna: –10 + 3 = –7   Así,   B + C = [ –5   –13 ]        [ –2   –7 ] 3) A – B   Restamos elemento a elemento:   • Primera fila, primera columna: 11 – (–4) = 11 + 4 = 15   • Primera fila, segunda columna: –9 – (–10) = –9 + 10 = 1   • Segunda fila, primera columna: 7 – (–3) = 7 + 3 = 10   • Segunda fila, segunda columna: –10 – (–10) = –10 + 10 = 0   Entonces,   A – B = [ 15   1 ]        [ 10   0 ] Resumen de resultados:  • A + B = [ 7  –19 ]       [ 4  –20 ]  • B + C = [ –5  –13 ]       [ –2  –7 ]  • A – B = [ 15  1 ]       [ 10  0 ]

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Bonus Knowledge

¡Claro! Vamos a realizar las operaciones solicitadas con las matrices A, B y C. Primero definimos las matrices: - \( A = \begin{bmatrix} 11 & -9 \\ 7 & -10 \end{bmatrix} \) - \( B = \begin{bmatrix} -4 & -10 \\ -3 & -10 \end{bmatrix} \) - \( C = \begin{bmatrix} -1 & -3 \\ 1 & 3 \end{bmatrix} \) 1. **Suma de A y B:** \[ A + B = \begin{bmatrix} 11 & -9 \\ 7 & -10 \end{bmatrix} + \begin{bmatrix} -4 & -10 \\ -3 & -10 \end{bmatrix} = \begin{bmatrix} 11 - 4 & -9 - 10 \\ 7 - 3 & -10 - 10 \end{bmatrix} = \begin{bmatrix} 7 & -19 \\ 4 & -20 \end{bmatrix} \] 2. **Suma de B y C:** \[ B + C = \begin{bmatrix} -4 & -10 \\ -3 & -10 \end{bmatrix} + \begin{bmatrix} -1 & -3 \\ 1 & 3 \end{bmatrix} = \begin{bmatrix} -4 - 1 & -10 - 3 \\ -3 + 1 & -10 + 3 \end{bmatrix} = \begin{bmatrix} -5 & -13 \\ -2 & -7 \end{bmatrix} \] 3. **Resta de A y B:** \[ A - B = \begin{bmatrix} 11 & -9 \\ 7 & -10 \end{bmatrix} - \begin{bmatrix} -4 & -10 \\ -3 & -10 \end{bmatrix} = \begin{bmatrix} 11 + 4 & -9 + 10 \\ 7 + 3 & -10 + 10 \end{bmatrix} = \begin{bmatrix} 15 & 1 \\ 10 & 0 \end{bmatrix} \] Así que los resultados de las operaciones son: - \( A + B = \begin{bmatrix} 7 & -19 \\ 4 & -20 \end{bmatrix} \) - \( B + C = \begin{bmatrix} -5 & -13 \\ -2 & -7 \end{bmatrix} \) - \( A - B = \begin{bmatrix} 15 & 1 \\ 10 & 0 \end{bmatrix} \)

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy